2006
DOI: 10.2975/29.2006.219.222
|View full text |Cite
|
Sign up to set email alerts
|

Which factors predict case management services and how do these services relate to client outcomes?

Abstract: The current study explores two issues: which factors predict case management services and which case management services predict outcomes. Thirty individuals with schizophrenia participated in the study. Information regarding clients' characteristics and the working alliance was collected within the first 2 months of participation in the program and again 1 year later. Case managers completed a daily contact log for each client over the course of the year. Results suggest that the working alliance is a strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…All included clinician-rated measures of functioning. Four associations (3 coded as bivariate, 1 as multivariate) related to global assessments of functioning [1,16,20], 2 of which were statistically significant [16,20]. One study used clinician and patient ratings of the TR and reported 2 associations with measures of occupational functioning [19].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All included clinician-rated measures of functioning. Four associations (3 coded as bivariate, 1 as multivariate) related to global assessments of functioning [1,16,20], 2 of which were statistically significant [16,20]. One study used clinician and patient ratings of the TR and reported 2 associations with measures of occupational functioning [19].…”
Section: Resultsmentioning
confidence: 99%
“…The substantial exclusions at this stage were due to a large number of studies that had assessed the TR, but not studied it as a predictor of subsequent outcome. Finally, 9 [14,15,16,17,18,19,20,21,22] of the 33 relevant papers were found to meet all inclusion criteria and were included in the review. The search process is summarised in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations